The Implementation of Creative Teaching in Literature Class in English Education Department Universitas Ahmad Dahlan Yogyakarta - Triyoga, Arilia; Akhsan, Nur Rifai (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
A lecturer or teacher is required to be very creative in order to make students motivated to learn. This study aims to explain the creative teaching that can be applied in literature classes in the English Education Department of Universitas Ahmad Dahlan. Moreover, this study also will explore the improvement of students’ motivation by implementing creative teaching in literature classes of English Education Department of Universitas Ahmad Dahlan. This research is a descriptive study. Observation is the initial activity that will be carried out in this study, and the data from this study were collected through a process of observation to find out its usefulness to students’ motivation for creative teaching in literature classes. The expected outcome of this research is that creative teaching can be applied well in the literature class at the English Education Department of UAD. Also, the positive benefits that can be learned from the implementation of creative teaching are the availability of materials in the form of podcasts and various activities in the teaching of literature class such as a gallery walk, creative writing, jigsaw, group discussions, role play, and others. Students’ motivation is pretty good for the implementation of these activities.